Pengaruh Pengalaman Pelanggan, Citra Merek dan Endorsement terhadap Kepuasan Pelanggan pada Kanarasa Coffee Banda Aceh - Syahputra, Muhammad; Tuwisna Tuwisna; Sulfitra Sulfitra (Jurnal Sains dan Ilmu Terapan, 2026)
This study aims to comprehensively analyze the influence of customer experience, brand image, and endorsement on customer satisfaction at Kanarasa Coffee Banda Aceh using a quantitative approach. The research data were collected through the distribution of questionnaires to 96 respondents who are active customers. Data analysis was conducted using various statistical techniques, including validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, as well as hypothesis testing through t-tests and F-tests to determine both partial and simultaneous effects. The results show that customer experience, brand image, and endorsement, both collectively and individually, have a positive and significant effect on customer satisfaction. These three variables contribute 32.3% to customer satisfaction, while the remaining percentage is influenced by other factors not examined in this study. Therefore, the effective management of customer experience, consistent strengthening of brand image, and the selection of appropriate and relevant endorsements are important factors in enhancing customer satisfaction at Kanarasa Coffee Banda Aceh in a sustainable manner.